PENGARUH TIDAK OPTIMALNYA KINERJA SISTEM PENGABUTAN BAHAN BAKAR PADA MESIN INDUK KAPAL SN 76 - Pramada, Alfath Dimas; Arifin, Syamsul; Kurniadi, Dedy; Mutamar, Rispa Saeful (Jurnal Maritim Malahayati, 2025)
The injector is an important component in the main engine that has an important role to influence the combustion system. The injector functions to spray and mist the fuel in the cylinder at the end of the compression stroke. If the results of spraying fuel form a perfect mist, this will facilitate the combustion process in the combustion chamber so that damage to the main engine can be reduced. The purpose of this study is to determine the causes, impacts, maintenance and repair of injectors on the main engine of the SN 76 ship. The research method used for this research is to use a qualitative descriptive method. The results obtained from this study indicate that the less than optimal work of the injector in dissolving fuel into the cylinder which has an impact on reducing performance and incomplete combustion, as for the solution of this problem is to try to optimize the work of the injector, namely injector maintenance according to working hours, repair according to the instruction manual book and handling spare parts.